Systematic notes on tribes in the family Caliscelidae (Hemiptera: Fulgoroidea) with the description of new taxa from Palaearctic and Oriental Regions - Gnezdilov, Vladimir M.; Wilson, Michael R. (Zootaxa, 2006)
A diagnosis of the family Caliscelidae Amyot et Serville, 1843 is given. The system of higher taxa of the family is revised. The genus Coinquenda Distant, 1916 is transferred to the subfamily Ommatidiotinae from the family Issidae. Coinquendini trib. nov. (type genus: Coinquenda Distant, 1916) is erected in the subfamily Ommatidiotinae. Coinquenda nigroclavata Distant, 1916 is redescribed. The tribe Adenissini Dlabola, 1980 is recharacterized and transferred to the subfamily Ommatidiotinae from the subfamily Caliscelinae. The rank of the tribe Bocrini Emeljanov, 1999 is reduced to the subtribe of the tribe Adenissini. As a result the genera Perissana Metcalf, 1952, Pterilia Stål, 1859, and Pterygoma Melichar, 1903 are transferred to the Adenissini from the family Issidae. Pteriliina subtrib. nov. (type genus: Pterilia Stål, 1859) is erected in the tribe Adenissini. Distantina gen. nov. (type species: Elidiptera fimlivata Walker, 1851) is erected in the subtribe Pteriliina subtrib. nov. Keys to the subfamilies, tribes, and subtribes of the Caliscelidae, the genera of the tribe Adenissini, and species of the genus Perissana Metcalf are given. Anissus Dlabola, 1980 and Denissus Dlabola, 1980 are placed in synonymy under Perissana Metcalf, 1952. Perissana jakowleffi (Puton, 1890) is redescribed. Adenissus circularis Dlabola, 1980 and Anissus bispinatus Dlabola, 1980 are transferred to the genus Perissana. Perissana dlabolai nom. nov. is proposed as a replacement name for Adenissus circularis Dlabola, 1980 (secondary homonym). Raunolina subgen. nov. (type species: Perissus circularis Linnavuori, 1952) is erected in the genus Perissana. Perissana (Raunolina) arabica sp. nov. is described from Saudi Arabia. 5 th instar larva of Adenissus riadicus Dlabola, 1985 is described. New faunistic records for 5 species of the family are provided.